Photovoice methodology in social work research - Semigina, Tetyana (Social work and education, 2022)
In recent decades, there has been a growing interest in the use of such a visual research method as photovoice. This article aims to characterize photovoice as a research methodology in social work. The study analyzed 30 full-text English-language publications, most of which were written by US researchers. The analysis of publications was based on the following criteria: (1) the general purpose of the photo voice as a methodology of research in social work and its philosophy; (2) stages and procedures for the use of photovoice, the role of researchers and other research participants; (3) examples of the use of photo voice in foreign social work; (4) the advantages and limitations of photovoice identified by researchers who have used this methodology in theirresearch. Photovoice is a participatory and reflective method of research in social work. Its main tasks include: to encourage research participants to express their own opinions; to form critical consciousness through group discussion; achieve policy change. Photovoice is based on: feminist theory; critical pedagogy; participatory approach to documentary photography. It uses transformational or emancipatory frameworks of analysis that focus on social change. The use of photovoice involves compliance with a number of successive stages, some of which may be repeated: the preparatory stage; introductory group session; work of research participants on photo collection; group discussion; preparation of the report; discussion of results; organization of an exhibition of works; conveying information to those on whom decision-making depends. Photovoice is used to study the needs of various vulnerable groups, especially those who are discriminated and whose voice is often ignored. This reflective method can also be useful in studying various aspects of social work practice.